1977
DOI: 10.1182/blood.v49.3.355.bloodjournal493355
|View full text |Cite
|
Sign up to set email alerts
|

Changing erythrocyte populations in juvenile chronic myelocytic leukemia: evidence for disordered regulation

Abstract: Fetal and adult erythrocyte characteristics were studied serially in a 30-mo-old female with juvenile chronic myelocytic leukemia. On presentation the erythrocytes exhibited predominantly fetal characteristics as indicated by 69% hemoglobin F (HbF), 1.1% hemoglobin A2 (HbA2), absent I antigen, and fetal levels of the erythrocyte enzymes, carbonic anhydrase I and II, glucose-6-phosphate dehydrogenase, hexokinase, pyruvate kinase, and lactate dehydrogenase; 100% of the erythrocytes present contained HbF. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Whether these findings can be reproduced in man remains to be determined, but there is evidence suggesting that both increased F-cell numbers and age dependent increased Hb F pcr F-cell occur in certain clinical situations. Increase in F-cells has been demonstrated in congenital hypoplastic anaemias (Alter, 1979) and during the recovery from transient erythroid hypoplasia (Sheridan et al, 1976;Alter, 1979), after phlebotomy (Papayannopoulou et a/, 1980), and an increase in the concentration of Hb F per cell was found in chronic juvenile myeloid leukaemia (Dover et a!, 1977). In patients with sickle cell anaemia the number of F-cells is increased, but in most cases the corpuscular concentration of Hb F is not high enough to inhibit sickling.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these findings can be reproduced in man remains to be determined, but there is evidence suggesting that both increased F-cell numbers and age dependent increased Hb F pcr F-cell occur in certain clinical situations. Increase in F-cells has been demonstrated in congenital hypoplastic anaemias (Alter, 1979) and during the recovery from transient erythroid hypoplasia (Sheridan et al, 1976;Alter, 1979), after phlebotomy (Papayannopoulou et a/, 1980), and an increase in the concentration of Hb F per cell was found in chronic juvenile myeloid leukaemia (Dover et a!, 1977). In patients with sickle cell anaemia the number of F-cells is increased, but in most cases the corpuscular concentration of Hb F is not high enough to inhibit sickling.…”
Section: Discussionmentioning
confidence: 99%
“…This has been best studied in patients with the juvenile form of chronic myelogenous leukemia, where there is a reversion from adult to fetal phenotype in hemoglobin (from Hb A to Hb F), carbonic anhydrase activity (decrease), and amount ofi. antigen on the cell surface (increase) [16][17][18][19][20] . The combined appearance of these fetal red cell characteristics have been attributed to a malignant proliferation of a "fetal" hemopoietic stem cell [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…J-CML differs in several features from adult type of CML. In particular, the high Hb F level (Hardisty et al, 1964;Weatherall et al, 1968) and the high frequency occurrence of F-cells (Dover et al, 1977) are well known. Our present observations show that all bursts are heterogenously committed to y chain synthesis but did not reveal discontinuous populations committed to synthesis of y or p chains and the distribution of y chain synthesis approached a normal distribution.…”
Section: Disc Us S I 0 Nmentioning
confidence: 99%
“…anhydrase activity (Hardisty et al 1964: Weatherall et al, 1968: Cao. 1976: Gahr etal, 1976Weatherall & Brown, 1970) and decreased titre of I antigen (Dover et al, 1977;Weatherall et al 1968). Altman et d ( 1 9 7 4 ) and Suda et al(1982) demonstrated that the growth patterns of granulocyte-macrophage colony forming cells in J-CML revealed a predominance of macrophage colonies (M-CFC).…”
mentioning
confidence: 99%
See 1 more Smart Citation